2015
DOI: 10.18546/ijdegl.07.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Modernity's 'other' and the transformation of the university

Abstract: In a dehumanized world in which meanings derived from dominant liberal world views are tacitly assumed to exist objectively and to impose themselves on discourses and on minds quite independently of who expresses them, this paper endorses what Immanuel Wallerstein calls 'unthinking social science' and then rethinking social science in the light of modernity's 'other'. We understand social science to include not just the academic fields discussed by Wallerstein like economics and political science, but also ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Is it politically meaningful for the company to achieve green development? e environment is ecologically transparent, and the political environment is excellent [24]. Under the premise of the enterprise's green development business philosophy, the gradual development of economic construction can increase the GDP income of the country and the people and achieve a win-win situation.…”
Section: Definition Of Enterprise Green Management Developmentmentioning
confidence: 99%
“…Is it politically meaningful for the company to achieve green development? e environment is ecologically transparent, and the political environment is excellent [24]. Under the premise of the enterprise's green development business philosophy, the gradual development of economic construction can increase the GDP income of the country and the people and achieve a win-win situation.…”
Section: Definition Of Enterprise Green Management Developmentmentioning
confidence: 99%
“…Indien die wetenskap sistematiese en herhalende patrone identifiseer, kan die samelewing wel sy pad verander en die voorspelbaarheid tot sy voordeel gebruik, en sodoende die menslike vermoë om sy lotsbestemming te beheer, versterk -ook deur Opvoedkundenavorsing. Die eenvoud van hierdie misleidende argument is netso optimisties as wat dit oortuigend is, en die resultaat is die formidabele wetenskaplike establishment wat grootliks ingespan word vir die opspoor, dokumentering en verduideliking van permanensie en verbygaande ervaring (Richards 2015).…”
Section: Emansipatoriese Leer As Herbedinkingunclassified
“…University all over the world are on the verge of transformation, most especially universities in the global south, this is to say that 21 st -century universities will operate better in the transformed system where modernity and modernisation in a positive direction become the order of the day. Modernity in university education bothers more on the new ways of doing things, while some conceptualised it to mean the western way of doing things (Eisenstadt, 2010;Gunn & Vernon, 2011;Richards, 2015). The fact from these thoughts confirmed that modernity in university education brings to all stakeholders the idea of new development, new ideas, innovations, transformations, and above all, devising new ways of "doing".…”
Section: Introductionmentioning
confidence: 99%